The Effects of Engage, Study, Activate (ESA) Method on 10 Year Students’ English-Speaking Ability - Azizah Hairunniza; Muhammad Asfah Rahman; Sultan Baa (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
The purpose of this research was to discover whether the use of the ESA Method in teaching speaking has effects or not. The pre-experimental design was the method used by the researchers with one group pre-test and post-test. The population was the tenth-grade students of SMAN 3 Makassar in the 2021/2022 academic year. The sample was taken by using a purposive sample technique that consisted of 30 students. The instrument of this research was a speaking test administered as a pre-test and post-test. The result of this research proved that there was a significant difference between students’ scores before treatment and students’ scores after treatment. The students' speaking ability after the implementation of ESA is increased or getting better than before the implementation of the ESA Method. It can be seen from the mean score, the mean score of students’ pre-tests was 61.64,0020and it was lower than the mean score of post-tests (74.73). The significant value of this research (0.000) was smaller than the significant level (0.05). It can be concluded that the use of the ESA method affects students’ speaking ability in terms of accuracy and fluency at the tenth-grade students of SMAN 3 Makassar.